Biotechnology and Biomaterial-Based Therapeutic Strategies for Age-Related Macular Degeneration. Part II: Cell and Tissue Engineering Therapies - Jemni-Damer, Nahla; Guedan-Duran, Atocha; Fuentes-Andion, María; Serrano-Bengoechea, Nora; Alfageme-Lopez, Nuria; Armada-Maresca, Félix; Guinea, Gustavo V.; Perez-Rigueiro, José; Rojo, Francisco; Gonzalez-Nieto, Daniel; Kaplan, David L.; Panetsos, Fivos (Frontiers in Bioengineering and Biotechnology, 2020)
Age-related Macular Degeneration (AMD) is an up-to-date untreatable chronic neurodegenerative eye disease of multifactorial origin, and the main causes of blindness in over 65 y.o. people. It is characterized by a slow progression and the presence of a multitude of factors, highlighting those related to diet, genetic heritage and environmental conditions, present throughout each of the stages of the illness. Current therapeutic approaches, mainly consisting on intraocular drug delivery, are only used for symptoms relief and/or to decelerate the progression of the disease. Furthermore, they are overly simplistic and ignore the complexity of the disease and the enormous differences in the symptomatology between patients. Due to the wide impact of the AMD and the up-to-date absence of clinical solutions, the development of biomaterials-based approaches for a personalized and controlled delivery of therapeutic drugs and molecules represents the main challenge for the defeat of this neurodegenerative disease. Here we present a critical review of the available and under development AMD therapeutic approaches, from a biomaterials and biotechnological point of view. We highlight benefits and limitations and we forecast forthcoming alternatives based on novel biomaterials and biotechnology methods. In this third part we review the preclinical and clinical cell-replacement approaches aiming at the development of efficient AMD-therapies, the employed cell types, as well as the cell-encapsulation and cell-implant systems. We discuss their advantages and disadvantages and how they could improve the survival and integration of the implanted cells.